Modern weapons and military equipment for issue 2-2016 - Vučković, Dragan M. (Vojnotehnički glasnik / Military Technical Courier, 2016)
Gulf shield Russian TV reveals torpedo-based nuclear system Kurganets 25 family undergoing trials Rafael refines Iron Beam ahead of procurement decisionRussian airborne forces to receive new SPRUT Overmatch: Rheinmetall pushes to enhance tank firepower Dead end? Wither now for Zumwalt's Advanced Gun System Turkey test armed UAV for first time Possible J-16 EW variant makes its maiden flight Geotech details through-wall detection systems